2001
DOI: 10.1530/eje.0.1440169
|View full text |Cite
|
Sign up to set email alerts
|

The pancreatic islets in spontaneously hypertensive rats: islet blood flow and insulin production

Abstract: The aim of the study was to investigate if hypertension affects pancreatic islet blood flow and endocrine function. For this purpose, spontaneously hypertensive rats (SHR) were compared with normotensive control Wistar±Kyoto rats (WKY). Both islet size and islet cell replication in 4-monthold SHR was increased compared with WKY. The (pro)insulin biosynthesis was reduced in islets isolated from SHR, whereas the insulin content was unchanged. A hyperinsulinemic response to glucose in vivo was observed in 4-and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Changes in pancreatic islet microcirculation may impede insulin output in diabetic subjects, and could contribute to the pathogenesis of the disease. Islet hyperperfusion and abnormal modulation of IBF (islet blood flow) after glucose challenge have been observed in various animal models of glucose intolerance and diabetes, including obese animals [3] as well as the non-obese GK (Goto-Kakizaki) rats [4].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in pancreatic islet microcirculation may impede insulin output in diabetic subjects, and could contribute to the pathogenesis of the disease. Islet hyperperfusion and abnormal modulation of IBF (islet blood flow) after glucose challenge have been observed in various animal models of glucose intolerance and diabetes, including obese animals [3] as well as the non-obese GK (Goto-Kakizaki) rats [4].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory mechanisms that control islet blood flow are complex and include neural, hormonal, and local mechanisms that are independent of the surrounding exocrine pancreas (5). It has been reported that islet blood flow is altered in rodent models with type 1 (6) or type 2 diabetes (7,8), obesity (9 -11), and hypertension (12). Although it has been suggested that changes in islet blood flow may be closely relevant to changes in islet function and metabolism, the relationship between flow and function is not fully understood.…”
mentioning
confidence: 99%
“…In spite of this, we saw no major changes in organ blood flows, besides an increase in adrenal, total pancreatic and islet blood flow. This is unlikely to be due to the increased mean arterial blood pressure, since we have previously shown that this is well within the interval in which these blood flow values are autoregulated (34). That also islet blood flow increases, is surprising in view of the sensitivity of islets to NO (see above).…”
Section: Discussionmentioning
confidence: 79%